STRESS AMONG BANKING EMPLOYEE- A LITERATURE REVIEW - M K., Manjunatha; Renukamurthy, T.P. (International Journal of Research -GRANTHAALAYAH, 2017)
For banking employees around the globe, stress on the job can be a challenge; stress can be sometimes positive and sometimes negative. Positive stress leads to productivity and negative stress leads to loss for the organization. There is already a certain level of stress in Banking employees work life and then encounter even more stress arising from the work pressure that Banking employees face on the job. Many employees cannot cope with such rapid changes taking place in the jobs. Role conflict, Service for customer, contribution, rapid technological change, lack of customer response is the great transaction of stress for the banking workers. The aim of this research is to understand roots and outcomes of job stress on the employee performance in banking sector.